Structure and weak hydrogen bonds in liquid acetaldehyde - Cordeiro, Maria A. M. [UNESP]; Cordeiro, João M. M. [UNESP] (FapUNIFESP (SciELO), 2004)
Monte Carlo simulations have been performed to investigate the structure and hydrogen bonds formation in liquid acetaldehyde. An all atom model for the acetaldehyde have been optimized in the present work. Theoretical values obtained for heat of vaporisation and density of the liquid are in good agreement with experimental data. Graphics of radial distribution function indicate a well structured liquid compared to other similar dipolar organic liquids. Molecular mechanics minimization in gas phase leads to a trimer of very stable structure. The geometry of this complex is in very good agreement with the rdf. The shortest site-site correlation is between oxygen and the carbonyl hydrogen, suggesting that this correlation play a important role in the liquid structure and properties. The O⋯H average distance and the C-H⋯O angle obtained are characteristic of weak hydrogen bonds.
Keywords: Acetaldehyde; Liquid structure; Monte Carlo simulation; Weak hydrogen bond; acetaldehyde; carbonyl derivative; hydrogen; organic compound; oxygen; atom; chemical structure; density; gas; geometry; heat; hydrogen bond; liquid; molecular mechanics; molecular model; Monte Carlo method; vaporization